Evaluation of tomato based agro-industrial byproducts as substrates for Trichoderma harzianum cultivation and bioinoculant potential - Esposito, Antonia; Scala, Valeria; Vassilev, Nikolay; Aragona, Maria; Canfora, Loredana; Polito, Alessandro; Fiorani, Riccardo; Mocali, Stefano (Frontiers in Microbiology, 2026)
Trichoderma harzianum is a well-known biocontrol agent with growing interest as a multifunctional bioinoculant due to its diverse metabolic capabilities. Despite its promising potential, the transition from laboratory-scale cultivation to industrial-scale production still presents challenges, particularly in optimizing biomass and spore yield at low cost. This study focused on testing a new medium for spore/mycelium production of T. harzianum integrating traditional growth media with gazpacho, a tomato-based by-product of Andalusian food as cheap substrate. We also assessed its multifunctional activity, including the tolerance to salt stress, solubilization of rock phosphate and the antagonistic activity against three major tomato pathogens (Botrytis cinerea, Fusarium oxysporum, and Pyrenochaeta lycopersici) through dual culture assays. The results showed that media supplemented with 3 and 6% (v/v) gazpacho significantly increased T. harzianum biomass and sporulation in solid and submerged state fermentations, while 10% reduced spore formation in liquid submerged fermentation. Interestingly, biomass and sporulation were further improved in media containing 3–6% (v/v) gazpacho combined with 100 mM NaCl. Trichoderma harzianum was able to grow and sporulate in solid media with up to 100 mM NaCl. Moreover, the strain showed phosphate solubilization activity on gazpacho-containing media in submerged fermentation, and effectively inhibited over 70% of pathogenic mycelial growth, with B. cinerea showing the highest inhibition (78.40%). Overall, these results highlight the improvement in biomass and spore production of T. harzianum grown in traditional growth media supplemented with 6% gazpacho, as well as its multifunctional activities under these fermentation conditions, thus representing a promising approach towards the production of cheap bioinoculants and supporting the circular economy in microbial technology. Furthermore, salt tolerance further encourage T. harzianum as a robust candidate for bioformulations in challenging agro-environment.